2011
DOI: 10.1158/1535-7163.mct-11-0469
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Radiation-Induced G2 Checkpoint Activation with the Wee-1 Inhibitor MK-1775 in Glioblastoma Cell Lines

Abstract: The purpose of this study was to determine the capacity of MK-1775, a potent Wee-1 inhibitor, to abrogate the radiation-induced G2 checkpoint arrest and modulate radiosensitivity in glioblastoma cell models and normal human astrocytes. The radiation-induced checkpoint response of established glioblastoma cell lines, glioblastoma neural stem (GNS) cells, and astrocytes were determined in vitro by flow cytometry and in vivo by mitosis-specific staining using immunohistochemistry. Mechanisms underlying MK-1775 ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 20 publications
5
87
0
1
Order By: Relevance
“…Previous studies have demonstrated the efficacy of inhibiting Wee1 in combination with DNA damaging agents, such as gemcitabine (3942) in the context of non-functional P53. MK-1775 monotherapy has been previously documented by Kreahling et al (30) where tumor explants treated with 500 nM MK-1775 for 24 hours demonstrated decreased CDK1 phosphorylation and features of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the efficacy of inhibiting Wee1 in combination with DNA damaging agents, such as gemcitabine (3942) in the context of non-functional P53. MK-1775 monotherapy has been previously documented by Kreahling et al (30) where tumor explants treated with 500 nM MK-1775 for 24 hours demonstrated decreased CDK1 phosphorylation and features of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…1B). MLN4924 also induced accumulation of p21, p27, inhibitor of G 2 -M phase transition Wee1 (26) and an increase in cyclin B, accompanied by a decrease in the level of phosphohistone H3 (p-H3), a hallmark of M-phase cells (27), indicating that MLN4924-treated cells were arrested at the G 2 phase (Fig. 1C).…”
Section: Neddylation Inhibition With Mln4924 Triggered G 2 Cell Cyclementioning
confidence: 92%
“…To determine at which phase MLN4924-treated cells were arrested, we detected the expression status of Wee1, a welldefined CRL/SCF substrate and an inhibitor of G 2 -M phase transition (35), as well as p-Histone H3 (p-H3, ser10), a hallmark of M phase cells (36). As shown in Fig.…”
Section: Mln4924 Induced G 2 Cell-cycle Arrest and Apoptosis In Livermentioning
confidence: 99%